The Mediating Role of Demographic Characteristics in the Relationship Between Mythical Thinking and Pathological Fear Among University Students - Yahya, Khatatbeh (Journal of Posthumanism, 2025)
This study examines the mediating function of demographic characteristics in the association between mythical thinking and pathological fear among university students in Saudi Arabia. The study involved 387 undergraduate students from various academic levels and socioeconomic backgrounds. We used standardized tools to gather data: the Mythical Thinking Scale, the Fear of Progression Questionnaire (FoP-Q), and a form for demographic information. Descriptive analysis indicated that students exhibited moderate to high levels of both mythical thinking (M = 83.8, 69.8%) and pathological fear (M = 120.4, 70.8%). Structural Equation Modeling (SEM) demonstrated that mythical thinking significantly forecasted pathological fear (B = 0.52, p < .001). Additionally, demographic factors including gender, marital status, and employment level functioned as partial mediators in this relationship. Gender exerted a significant direct influence on both pathological fear and mythical thinking, whereas marital status and employment level demonstrated particular effects on myth-related cognition. The model fit indices (GFI = 0.912, CFI = 0.916) showed that the proposed model was strong. These results indicate that students exhibiting elevated levels of pathological fear are more prone to adopt myth-based cognitive styles, with such tendencies differing among demographic subgroups. The research emphasizes the necessity for culturally and demographically attuned mental health interventions aimed at addressing irrational belief systems as a strategy for mitigating pathological fear within academic environments.